Development of an online slide library - Fernandes, Sílvia; Duarte, Raquel; Silva, Regina Augusta (Citotech Online - Case Review, 2015)
Digital Cytology consists in the conversion of a glass slide into a digital image. The application of digital cytology in education, conferences, telecytology, publications and cytology websites has shown increased accessibility to cytology, along with the quality and efficiency improvement of the health services. In this study we intend to develop an Online Slide Library of gynecological cytology available to students for the gynecological cytology One hundred samples of gynecological cytology were selected and scanned by the whole slide imaging method. The Online Slide Library was created with HyperText Markup Language 5 and the digital images sharing within the Library was conducted using the institution network server. In education, the Online Slide Library developed allows the easier access to the study of gynecologic cytology as well as the access to rare and/or old samples. Also several students can observe the same case simultaneously with this method of digital cytology. The results of the present work allow to conclude that the Online Slide Library is a complementary tool for the gynecological cytology study.